2020
DOI: 10.1177/1057083720928496
|View full text |Cite
|
Sign up to set email alerts
|

Early Socialization and Opinions of Musicianship Among Preservice Music Teachers

Abstract: The development of musicianship is a fundamental learning outcome for music students. The purpose of this study was to examine the early socialization experiences of preservice music teachers, as well as their opinions about musicianship. A total of 138 undergraduate music education students completed a three-part online questionnaire. The large ensemble setting was the most common source of learning and participants believed this setting contributed to the development of overall musicianship more so than any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Given the notion that experience is necessary for preservice teachers to reflect on their teaching and, thus, project those experiences to future teaching episodes, many colleges and universities provide students ACL opportunities in the form of field experiences. Previous music education researchers have cited the importance and impact on field experience in the development and socialization of preservice music teachers (Isbell, 2006; Paul et al, 2001). Because New Horizons ensemble members’ ability levels—and perhaps those of other community music ensembles—often reflect those of beginning and/or intermediate grade school students, teaching in such settings can represent a realistic avenue for preservice teachers to obtain meaningful field experiences that reflect future school music environments.…”
Section: Discussionmentioning
confidence: 99%
“…Given the notion that experience is necessary for preservice teachers to reflect on their teaching and, thus, project those experiences to future teaching episodes, many colleges and universities provide students ACL opportunities in the form of field experiences. Previous music education researchers have cited the importance and impact on field experience in the development and socialization of preservice music teachers (Isbell, 2006; Paul et al, 2001). Because New Horizons ensemble members’ ability levels—and perhaps those of other community music ensembles—often reflect those of beginning and/or intermediate grade school students, teaching in such settings can represent a realistic avenue for preservice teachers to obtain meaningful field experiences that reflect future school music environments.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal records of both the novice teachers in this study illustrated their trajectories of academic literacy development and explained how these experiences had impacted their perceptions of their roles and identities in educational settings. Such perception, known as self-perception as teachers, refers to how teachers view or perceive themselves in their professional role as educators ( Isbell, 2008 ). Both subjects found that the pedagogical knowledge and theories they acquired in various courses informed their teaching methods and developed their identities as researcher-teachers in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with a study of 138 preservice music teachers who were asked to share information about their early socialization and opinions of musicianship. 11 Their learning took place primarily in the large ensemble, on a single instrument, and they prioritized reading and analyzing music notation over improvisation, composing, or learning songs by ear.…”
Section: Developing Musicianshipmentioning
confidence: 99%